PENERAPAN CRM UNTUK MENINGKATKAN LOYALITASPELANGGAN - Yasmine Sekarkinasih Hardiana; Tangguh Dwi Pramono (Ebiz Prima Nusa, 2022)
This article provides information on implementing CRM to increase customer loyalty. The use of CRM and its tools are useful to make it easier for business actors to continue to reach every customer, improve customer relationships and maintain customer relationships. The importance of using CRM and its tools is that business actors can continue to provide the latest innovations, improve services and continue to establish good relationships with customers in order to create customer loyalty. Customer loyalty is important for the survival of a business, with loyalty with them making regular purchases, recommending products or services offered by the company can help companies to continue to survive in the long term and have strong customers.